Management of the Village Revenue and Expenditure Budget in Corawali Village, Sidrap Regency - Sri Wahyuni; Muh. Nasrullah; Nasir Nasir; Fahmi Surya Abdi (ASHA Publishing, 2025)
The village revenue and expenditure budget is prepared to manage village finances in a transparent and accountable manner to improve community welfare. This study aims to evaluate the management of the village revenue and expenditure budget in Corawali Village, Sidenreng Rappang Regency, from the perspective of transparency and accountability. Using a qualitative descriptive approach, data was obtained from village officials, members of the village consultative body, and the community through in-depth interviews, participatory observations, and document studies. Data analysis techniques include data reduction, presentation, and qualitative verification. The research focuses on four main aspects: planning, implementation, reporting, and accountability. The results indicate that the management of the village revenue and expenditure budget has gone quite well with the community's involvement in village deliberations and program implementation. However, participation is uneven because of a limited understanding of technical information. Reporting is carried out routinely through the Siskeudes application, although it has not been fully socialized effectively. Accountability is carried out openly through village forums and information media, but the presentation of information still needs to be simplified, and human resources a